The Novel Glutamine Antagonist Prodrug JHU395 Has Antitumor Activity in Malignant Peripheral Nerve Sheath Tumor - Lemberg, Kathryn M; Zhao, Liang; Wu, Ying; Veeravalli, Vijayabhaskar; Alt, Jesse; Aguilar, Joanna Marie H; Dash, Ranjeet P; Lam, Jenny; Tenora, Lukáš; Rodriguez, Chabely; Nedelcovych, Michael T; Brayton, Cory; et al. (Molecular cancer therapeutics, 2020)
The carbon and nitrogen components of glutamine are used for multiple biosynthetic processes by tumors. Glutamine metabolism and the therapeutic potential of glutamine antagonists (GA), however, are incompletely understood in malignant peripheral nerve sheath tumor (MPNST), an aggressive soft tissue sarcoma observed in patients with neurofibromatosis type I. We investigated glutamine dependence of MPNST using JHU395, a novel orally bioavailable GA prodrug designed to circulate inert in plasma, but permeate and release active GA within target tissues. Human MPNST cells, compared with Schwann cells derived from healthy peripheral nerve, were selectively susceptible to both glutamine deprivation and GA dose-dependent growth inhibition. In vivo, orally administered JHU395 delivered active GA to tumors with over 2-fold higher tumor-to-plasma exposure, and significantly inhibited tumor growth in a murine flank MPNST model without observed toxicity. Global metabolomics studies and stable isotope-labeled flux analyses in tumors identified multiple glutamine-dependent metabolites affected, including prominent effects on purine synthesis. These data demonstrate that glutamine antagonism is a potential antitumor strategy for MPNST.
Keywords: nádorové buněčné linie; Xenograft Model Antitumor Assays; Disease Models, Animal; mužské pohlaví; Mice; Cell Line, Tumor; Glutamine; Prodrugs; modely nemocí na zvířatech; ženské pohlaví; xenogenní modely - testy protinádorové aktivity; zvířata; Humans; prekurzory léčiv; myši; glutamin; nádory nervové pochvy; Female; Nerve Sheath Neoplasms; lidé; Male; Animals